USES OF JUSTICE AND ARBITRATION OF DISPUTES IN THE OLD REGIME: EXPERIENCES IN THE HISPANIC MONARCHY - Mantecón Movellán, Tomás (Revista de Historia Social y de las Mentalidades, 2016)
By analyzing legal and political literature referring to the Hispanic Monarchy as well as by studying judicial cases and practices, this article explains social uses of justice and ways of settling conflicts in the Old Regime. This research gives new perspectives on justice as very much socially participated. At the same time, by stressing this socially focused perspective, this article shows the public peace building as a broader phenomenon from which it is frequently shaped from political history and history of law, giving new perspectives to reconsider the so-called historical judicial or legal revolution in Old Regime Western societies